Tip of the Spear : Land, Labor, and US Settler Militarism in Guåhan, 1944-1962 - Flores, Alfred Peredo, 1980- (Book collections on Project MUSE., 2023)
"This book utilizes the concept of settler militarism to investigate how the island of Guåhan was transformed from a pre-World War II coaling station into a major U.S. military site that was used to wage military operations during the Cold War"--